2022
DOI: 10.3390/ijms23095248
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin as a Human Genome “Guardian”—An Overall Point of View

Abstract: Structural abnormalities causing DNA modifications of the ethene and propanoadducts can lead to mutations and permanent damage to human genetic material. Such changes may cause premature aging and cell degeneration and death as well as severe impairment of tissue and organ function. This may lead to the development of various diseases, including cancer. In response to a damage, cells have developed defense mechanisms aimed at preventing disease and repairing damaged genetic material or diverting it into apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 188 publications
0
16
0
Order By: Relevance
“…The immunomodulatory effect of Lf lies in its ability to modulate innate and adaptive immunity. One of the most interesting properties of Lf is that it can reach the nucleus as Lf possesses the ability to bind specifically to the LfR, which also gives Lf great potential to deliver macromolecules to the cytoplasm and nucleus, such as nucleic acids (siRNA, mRNA, shRNA, and DNA) ( 98 ). Lf is also used as a non-viral vector to deliver anti-cancer and anti-bacterial drugs for targeted therapeutic purposes.…”
Section: Discussion and Prospectmentioning
confidence: 99%
“…The immunomodulatory effect of Lf lies in its ability to modulate innate and adaptive immunity. One of the most interesting properties of Lf is that it can reach the nucleus as Lf possesses the ability to bind specifically to the LfR, which also gives Lf great potential to deliver macromolecules to the cytoplasm and nucleus, such as nucleic acids (siRNA, mRNA, shRNA, and DNA) ( 98 ). Lf is also used as a non-viral vector to deliver anti-cancer and anti-bacterial drugs for targeted therapeutic purposes.…”
Section: Discussion and Prospectmentioning
confidence: 99%
“…LTF protein plays an important role as a transcription factor and triggers the expression of a variety of genes, including genes related to the innate immune response, lipid metabolism, the inhibition of angiogenesis, apoptosis induction, DNA repair and cell cycle regulation [ 9 ]. There are only a few studies investigating the link between LTF gene polymorphisms and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that LTF has anticancer properties and suppresses the metastatic potential of cancer. LTF arrests the G1 to S phase transition of the cell cycle due to an induced expression and/or activity of critical cell cycle regulatory proteins, including Akt, p21, p19, p27, Cdk2, cyclin E, Cdk4 and cyclin D1 [ 8 , 9 ]. In addition, it has been shown that bovine LTF exerts a cytotoxic effect on fibrosarcoma and melanoma as well as head and neck and colon cancer cells and inhibits the proliferation of lung cancer cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTF encode lactotransferrin. This glycoprotein arrested the G1 to S phase transition and it regulates the expression and function of proteins such as Akt, p21, p19, p27, Cdk2, cyclin E, Cdk4, and cyclin D1 [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%